2013
DOI: 10.1097/mcd.0b013e3283590986
|View full text |Cite
|
Sign up to set email alerts
|

Negative mutation screening of the NOG, BMPR1B, GDF5, and FGF9 genes indicates further genetic heterogeneity of the facioaudiosymphalangism syndrome

Abstract: We report on a patient with a clinical phenotype showing all the features of the multiple synostoses syndrome or the facioaudiosymphalangism syndrome, including symphalangism, condunction deafness, and the typical facies. Previously, it was shown that this condition is genetically heterogeneous with initially mutations described in the NOG gene, coding for Noggin, an extracellular antagonist of bone morphogenetic proteins. Noggin also interacts with growth differentiation factor 5 (GDF5), in which mutations ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Such negative molecular data for family 3 indicate that there may be further genetic heterogeneity underlying SYNS1, with the involvement of at least one additional gene. In fact, two studies by Dawson et al 12 and van den Ende et al 26 found no mutations in either NOG or GDF5 in the patient with NOG-SSD. Moreover, they did not find any mutations in NOG, BMPR1B, GDF5 or FGF9 in a patient with a clinical phenotype showing features of SYNS1 or facioaudiosymphalangism, suggesting further genetic heterogeneity for these syndromes.…”
Section: Nog Mutations and Diseasesmentioning
confidence: 96%
“…Such negative molecular data for family 3 indicate that there may be further genetic heterogeneity underlying SYNS1, with the involvement of at least one additional gene. In fact, two studies by Dawson et al 12 and van den Ende et al 26 found no mutations in either NOG or GDF5 in the patient with NOG-SSD. Moreover, they did not find any mutations in NOG, BMPR1B, GDF5 or FGF9 in a patient with a clinical phenotype showing features of SYNS1 or facioaudiosymphalangism, suggesting further genetic heterogeneity for these syndromes.…”
Section: Nog Mutations and Diseasesmentioning
confidence: 96%